Hypothesis Testing on Environmental Kuznets Curve of Agricultural Sector in Java Island: Panel Data Analysis - Ali Hasyim Al rosyid; Irham Irham; Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2017)
One obstacle in the improvement of community welfare in the agricultural sector, especially in Java, is the environmental externality which constantly exists in every economic activity. The objective of this research was to estimate greenhouse gas emission coming from agricultural sector in Java and identify whether farmers in Java had allocated environmental conservation costs as the impact of greenhouse gas emission from agricultural activities in Java. The inventory method of greenhouse gas emission from agricultural sector is based on inventory guidelines published by IPCC (Intergovernmental Panel on Climate Change) in 2006. As for the analysis to determine the relationship between greenhouse gas emission and GRDP of agricultural subsector per agricultural labor, The Environmental Kuznets Curve (EKC) was employed, alongside greenhouse gas emission indicators representing environmental degradation and GRDP of agricultural subsector per agricultural worker representing of per capita income of agricultural. Overall, greenhouse gas emissions, both CH4 methane emissions and carbon dioxide emission (CO2) - produced from rice cultivation, fertilizer application, livestock enteric fermentation and poultry manure - are gradually increasing. And the relationship between greenhouse gas emission and GRDP per worker has inverted-U shape; and it is in line with EKC hypothesis. Thereby, the role of the entire community elements and government support in implementing mitigation technology and agricultural adaptation is needed to cope with impacts of greenhouse gas emission, such as climate change.